Maternal risk factors and perinatal outcomes in fetal growth restriction using obstetric Doppler in South Kerala, India - T., Heera Shenoy; James, Sonia X.; T., Sheela Shenoy (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Fetal Growth Restriction (FGR) is the single largest contributing factor to perinatal morbidity in non-anomalous foetuses. Synonymous with Intrauterine Growth Restriction (IUGR), it is defined as an estimated fetal weight less than the10th percentile. Obstetric Doppler has helped in early detection and timely intervention in babies with FGR with significant improvements in perinatal outcomes. Hence, authors evaluated the maternal risk factors and diagnosis-delivery intervals and perinatal outcomes in FGR using Doppler. Methods: This research conducted in a tertiary care hospital in South Kerala included 82 pregnant women who gave birth to neonates with birth weight less than the 10th percentile over a period of1 year (Jan 1, 2017-Dec 31, 2017). Socio-demographic, maternal risk, Diagnosis- delivery interval in FGR and neonatal morbidities were studied. Results: Mean GA at diagnosis in weeks was 34.29 and 35.19 respectively for abnormal and normal Doppler respectively (p value-0.032). The mean birthweight in Doppler abnormal FGR was 272.34 g lesser than in Doppler normal group (p value-0.001). Growth restricted low birth weight neonates had Doppler pattern abnormalities (p value-0.0009). FGR <3rd percentile and AFI <5 had abnormal Doppler (OR:6.7). Abnormal biophysical profile (OR:14) and Non-Reactive NST (OR:3.5) correlated with abnormal Doppler. Growth restricted with normal Doppler had shorter NICU stays than with abnormalities (p value-0.003). Term FGR went home early than early preterm. (p value-0.001). Conclusions: Abnormal Doppler velocimetry is significantly associated with earlier FGR detection, shorter decision- delivery interval, reduction in the mean birthweight and longer NICU stay. Hence, Umbilical artery Doppler and Cerebroplacental index is an integral part of in-utero fetal surveillance to identify impending fetal hypoxia, appropriate management, optimising the timing of delivery and improve perinatal health in FGR.